The fundamentals of signal transmission : in line, waveguide, fibre, and free space - Ibbotson, L.; ScienceDirect eBooks (London : Arnold, 1999)
'The Fundamentals of Signal Transmission' presents a discussion of the main forms of signal transmission media. Twisted pair, coaxial line, optical fibre, waveguides and freespace propagation and antennas are covered using a standard format. After a discussion of signals in general, the nature of wave propagation is examined. These fundamentals are then related to the specific transmission types. Mathematics is kept as simple as possible and is complemented by ample qualitative explanation; where necessary more detailed mathematics can be found in the appendices. Some knowledge of basic electronic circuit theory and field theory is assumed. Written in an informal and accessible style, 'The Fundamentals of Signal Transmission' provides all undergraduate electronics engineers with a concise overview of electromagnetic signal transmission. written in an iformal and accessible style provides a concise overview of electromagnetic signal transmission covers all the main types of signal transmission in one volume.
Signals and waves * Twin-wire transmission line * Electromagnetic waves * Coaxical line, strip line and wave guides * Optical fibre * Free space * Further insights using the Smith chart * Solutions to problems.
Includes index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Signal processing -- Mathematical models; Signal theory (Telecommunication) -- Mathematics; Signal processing -- Mathematical models; Signal theory (Telecommunication) -- Mathematics; Electronic books